Efektivitas Komposting Sampah Organik untuk Mengatasi Limbah Rumah Tangga Desa Madiredo Kecamatan Pujon Kabupaten Malang - Kurniawati Meylianingrum (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Waste is the biggest problem on earth. Environmentalist organizations and local governments have socialized the environmental love movement on all fronts. It must also be supported by the first sector of waste producers, namely households. The method used in this community service is the 3R method: reduce, reuse, and recycle. The result of this service is to invite the household community to sort between organic and non-organic waste and then separate it at the time of disposal of the main waste at home. Next is to take advantage of still suitable waste and divert it to other use values. Furthermore, the last one is to recycle waste with practical value and a selling point. With this community service, it is hoped that it can reduce the volume of waste on earth and minimize the impact of waste on the environment.